Engineering problem-solving 101 : time-tested and timeless techniques - Messler, Robert W., Jr., 1942- (McGraw-Hill, 2013)
Contains more than 50 systematic approaches spanning all disciplines, logically organized into mathematical, physical/mechanical, visual, and conceptual categories. Strategies are reinforced with practical reference tables, technical illustrations, photographs, and real-world examples.